Hanna who fell from the sky [large type] - Meades, Christopher (Thorndike Press, 2017)
Hanna has never been outside her secluded community of Clearhaven. She has never questioned why her father has four wives or why she has fourteen brothers and sisters. And in only one week, on her eighteenth birthday, Hanna will follow tradition and become the fifth wife of a man more than twice her age. But just days before the wedding, Hanna meets an enigmatic stranger who challenges her to question her fate and follow her own will. And when her mother reveals a secret - one that could grant her the freedom she's known only in her dreams - Hanna is forced to decide whether she was really meant for something greater than the claustrophobic world of Clearhaven. But can she abandon her beloved younger sister and the only home she's ever known? Or is there another option - one too fantastical to believe?